Avaliação do cuidado prestado a pacientes diabéticos em nível primário Assessment of diabetic patient management at primary health care level - Rejane B. Araújo; Iná dos Santos; Marcelo A. Cavaleti; Juvenal S. D. da Costa; Jorge U. Béria (Universidade de São Paulo, 1999)
OBJETIVO: Descrever características de pacientes diabéticos acompanhados em um posto de atenção primária à saúde. MÉTODOS: Estudo transversal. Rastrearam-se 3.024 prontuários de família, em busca de pacientes com 30-75 anos, com diagnóstico de diabetes, atendidos nos últimos cinco anos. Os pacientes detectados foram entrevistados em seus domicílios, e compareceram ao posto para o exame físico e requisição para dosagem da hemoglobina glicosilada. RESULTADOS: A prevalência de diabetes foi de 4,2%. A maioria eram mulheres brancas, ±50 anos de idade, com renda familiar mensal <= 3 salários-mínimos. Menos de um terço seguia dieta; e, apenas um quinto fazia exercícios regulares. Cerca de 70% estavam em uso de hipoglicemiantes orais ou insulina. Dos que fizeram o exame (adesão de 70%), a maioria apresentou níveis normais ou aceitáveis de glicemia. CONCLUSÕES: Maior esforço deve ser dispendido pelas equipes de saúde de forma a promover a adesão dos pacientes diabéticos à dieta e ao exercício. OBJECTIVE: The characterization of diabetic patients seen at a primary health care clinic. METHODS: The case notes of 3,024 families were searched by means of a cross-sectional study for patients 30 to 75 years of age with a diagnosis of diabetes mellitus who had had a medical consultation during the previsous five years. These patients were interviewed at their homes and were asked to come to the health center for physical examination and a plasma glucose test using glucosylated hemoglobin (GH). RESULTS: The prevalence of diabetes was 4%. The typical diabetic patient was a white women, ±50 years of age, from a family with a monthly income <= 3 minimum wages. Compliance with GH was observed in 70% of the patients. Diet therapy was followed by less than one third of the patients and only one fifth were engaged in regular exercise. Nearly 70% were undergoing drug therapy (oral hypoglicemic agents or insulin); of these, only 15% used insulin. Most of the patients (66%) who agreed to have the GH test showed normal or fair glucose blood levels. CONCLUSIONS: Great efforts should be made by health teams to enhance diabetic patient education in order to promote compliance with recommendations regarding diet and exercise.